Just listen a novel - Dessen, Sarah (New York Viking Children's Books, 2006)
Isolated from friends who believe the worst because she has not been truthful with them, sixteen-year-old Annabel finds an ally in classmate Owen, whose honesty and passion for music help her to face and share what really happened at the end-of-the-year party that changed her life
1
Keywords: Family problems -- Fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Models (Persons) -- Fiction; Schools -- Fiction; Self-actualization (Psychology) -- Fiction